Budaya Baca Tulis Dan Kemampuan Berbahasa Asing Siswa Melalui Program Gerakan Literasi Madrasah (GELEM) - Siti Niswatun Chasanah; Rohana Maryam; Ali Sukamtono (Arsy : Jurnal Studi Islam, 2022)
The aim of this research is to create a Madrasah environment to become a lifelong learning environment by cultivating good reading, listening, writing and speaking activities. The research approach is a mixed method combining qualitative and quantitative using random sampling and interview techniques. Sampling is based on the calculation of 10% of the population, thus getting 46 samples. The population in this study were all students of MTsN 16 Jombang. The data collection technique was by distributing questionnaires. The results showed that there was an effect of literacy on students' foreign language skills through the madrasah literacy movement program